2021
DOI: 10.3390/pr9030424
|View full text |Cite
|
Sign up to set email alerts
|

Sage (Salvia officinalis L.) Essential Oil as a Potential Replacement for Sodium Nitrite in Dry Fermented Sausages

Abstract: This study investigates the effects of sodium nitrite replacement by the sage essential oil (SEO), on the physico-chemical, microbiological and sensory quality of dry fermented sausages (DFS) during 225 days of storage. The SEO (0.00, 0.05 and 0.10 µL/g) was added in DFS batters formulated with different levels of pork back fat (15% and 25%) and sodium nitrite (0, 75 and 150 mg/kg). The inclusion of SEO had no negative impact on pH, color (instrumental and sensory) and texture parameters. Total plate counts we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 46 publications
(92 reference statements)
6
7
1
Order By: Relevance
“…The CEO addition affected ( p < .05) increase of hardness and chewiness. These data are in contrary with those reported in our previous studies, where we showed that the same concentrations of juniper (Tomović et al., 2020) and sage essential oil (Šojić et al., 2021) had no effect on analyzed texture attributes. Decreased tenderness of meat products could be the result of protein oxidation and the creation of protein cross‐links (Jongberg et al., 2013), despite the addition of essential oils whose main goal was to inhibit both lipid and protein oxidative deterioration.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The CEO addition affected ( p < .05) increase of hardness and chewiness. These data are in contrary with those reported in our previous studies, where we showed that the same concentrations of juniper (Tomović et al., 2020) and sage essential oil (Šojić et al., 2021) had no effect on analyzed texture attributes. Decreased tenderness of meat products could be the result of protein oxidation and the creation of protein cross‐links (Jongberg et al., 2013), despite the addition of essential oils whose main goal was to inhibit both lipid and protein oxidative deterioration.…”
Section: Resultscontrasting
confidence: 99%
“…The obtained results confirmed synergistic effect of sodium nitrite (75 mg/kg) and CEO (0.10 µl/g) in increased redness of low‐fat dry‐fermented sausages. Similarly, in our previous studies we determined that essential oil obtained from juniper (Tomović et al., 2020) and sage (Šojić et al., 2021) efficiently improved the redness of dry‐fermented sausages produced with different levels of sodium nitrite. Beside traditional colorimeter (Minolta), color values of the meat products could be measured using computer vision system.…”
Section: Resultssupporting
confidence: 60%
“…Essential oils (EOs) are natural compounds, proved to have antimicrobial and antioxidant activity (Mohajer et al, 2021), and have been widely used in processed meats due to their beneficial effects (Šojić et al, 2021; Tomović et al, 2020). Addition of Eos to sausages formulation improves their microbial and chemical stability and safety (Šojić et al, 2021; Viuda‐Martos et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Essential oils (EOs) are natural compounds, proved to have antimicrobial and antioxidant activity (Mohajer et al, 2021), and have been widely used in processed meats due to their beneficial effects (Šojić et al, 2021; Tomović et al, 2020). Addition of Eos to sausages formulation improves their microbial and chemical stability and safety (Šojić et al, 2021; Viuda‐Martos et al, 2010a). Microencapsulation of Eos has progressed remarkably in recent years and could provide several benefits, including controlled release, reduced volatility, increased availability, solubility, stability, and bioavailability (increased antimicrobial and antioxidant activities; Abd Manaf et al, 2015; Viacava et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Caffeic acid derivatives and widely distributed flavonoids, occurring mainly in the form of flavones (e.g., apigenin, luteolin and their respective 6-hydroxylated derivatives), flavonols and their glycosides (e.g., kaempferol and quercetin), play a significant role in sage activity [36,37]. By the presence of the mentioned components, the plant is attributed with antioxidant, antimicrobial, antiproliferative and anticarcinogenic properties [38]. Its ability to inhibit bone tissue resorption seems to be of particular interest [39].…”
Section: Introductionmentioning
confidence: 99%